Postauricular reflexes elicited by soft acoustic clicks and loud noise probes: Reliability, prepulse facilitation, and sensitivity to picture contents. (6th September 2016) - Aaron, Rachel V.; Benning, Stephen D.
Abstract: The startle blink reflex is facilitated during early picture viewing, then inhibited by attention during pleasant and aversive pictures compared to neutral pictures, and finally potentiated during aversive pictures specifically. However, it is unclear whether the postauricular reflex, which is elicited by the same loud acoustic probe as the startle blink reflex but enhanced by appetitive instead of defensive emotion, has the same pattern and time course of emotional modulation. We examined this issue in a sample of 90 undergraduates using serially presented soft acoustic clicks that elicited postauricular (but not startle blink) reflexes in addition to standard startle probes. Postauricular reflexes elicited by both clicks and probes correlated during food and nurturant contents, during which they were potentiated compared to neutral pictures, suggesting clicks effectively elicit emotionally modulated postauricular reflexes. The postauricular reflex was initially facilitated during the first 500 ms of picture processing but was larger during pleasant than neutral pictures throughout picture processing, with larger effect sizes during the latter half of picture processing. Across reflexes and eliciting stimuli, measures of emotional modulation had higher coefficient alphas than magnitudes during specific picture contents within each valence, indicating that only emotional modulation measures assess higher‐order appetitive or defensive processing.